2014
DOI: 10.1371/journal.pone.0107154
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Combination of Gemcitabine and Dietary Molecule Induces Apoptosis in Pancreatic Cancer Cells and Down Regulates PKM2 Expression

Abstract: Gemcitabine, an effective agent in treatment of cancer of pancreas, has undergone failures in many instances after multiple cycles of therapy due to emergence of drug resistance. Combination of dietary compounds with clinically validated drugs has emerged as an effective therapeutic approach to treat pancreatic tumors, refractory to gemcitabine therapy. In order to optimize a possible synergistic combination of Gemcitabine (GCB) with dietary molecules, Betuilnic acid (BA) and Thymoquinone (TQ), stand-alone IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…The CI values of all DOX/TPL combinations (1/0.05, 1/0.1, 1/0.2, 1/0.5, and 1/1) were simulated with a reported method. 37,38 Most of the DOX/TPL combinations showed synergistic effect (CI ,1) for all treatment concentrations ( Figure 2B). Moreover, when the weight ratio of TPL/DOX decreased from 1/1 to 0.2/1, the CI decreased from 0.433 to 0.114 (Figure 3).…”
Section: Results and Discussion Synergistic Cytotoxicity Of Dox And Tmentioning
confidence: 98%
“…The CI values of all DOX/TPL combinations (1/0.05, 1/0.1, 1/0.2, 1/0.5, and 1/1) were simulated with a reported method. 37,38 Most of the DOX/TPL combinations showed synergistic effect (CI ,1) for all treatment concentrations ( Figure 2B). Moreover, when the weight ratio of TPL/DOX decreased from 1/1 to 0.2/1, the CI decreased from 0.433 to 0.114 (Figure 3).…”
Section: Results and Discussion Synergistic Cytotoxicity Of Dox And Tmentioning
confidence: 98%
“…Importantly, some reports showed that BA induced cell death by downregulating the expression of the P13K/Akt signaling pathway [ 19 ]. BA exhibits significant antitumor activities in various cancer cells, including pancreatic cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same research team also reported that Rauwolfia vomitoria extract can potentiate gemcitabine's anti-tumor effects, via reduction in tumor burden and prevented metastatic potential in an orthotopic pancreatic cancer mouse model [49]. Alternative study by Archana Pandita and coworkers suggested that gemcitabine may synergise with betulinic acid and thymoquinone, both of which are common dietary compounds, by inhibiting the proliferation of pancreatic cancer cells, inducing apoptosis and down-regulating pyruvate kinase M2 isoforms [50]. Irofulven (a compound from sesquiterpene mushroom metabolites) [51], cucurbitaicin B (Cucurbitacae family) were some of the pure compounds isolated from plants that can enhance the anti-tumor effects of gemcitabine [52].…”
Section: Discussionmentioning
confidence: 96%
“…Abbreviations ANOVA: One-way analysis of variance; Bax: Bcl-2-associated X protein; Bcl-2: B-cell lymphoma 2; BID: Bcl-2 homology 3 interacting domain death agonist; CI: Combination index; cIAP-2: Cellular inhibitor of apoptosis 2; DMSO: Dimethylsulfoxide; DRI: Drug reduction index; ELISA: Enzyme-linked immunosorbent assay; EOHSA: Excess Over Highest Single Agent; Gem: Gemcitabine; HSA: Highest Single Agent; IC 50…”
mentioning
confidence: 99%